Potential of acacia gum as a prebiotic ingredient through In vitro studies using human faecal microbiota - Rawi, Muhamad Hanif (2020)
There is a growing consensus of acacia gum, it is currently marketed as functional food to improve overall human health particularly the gut. This natural product of Acacia tree is the branched polysaccharide gummy exudate made up of complex biopolymer of arabinose and galactose monosaccharides. It is widely used in African countries and in the Middle East as a traditional medicine. Recently, the consumption of acacia gum has been related to potential health benefits. In terms of its potential prebiotics properties, this may be particular relevant to treat stomach disease. Thus, in this research commercially available acacia gum was investigated in vitro to assess its prebiotic potential. The studied acacia gum was from two different species; Acacia senegal and A. seyal. The experiment employed an in vitro batch culture using colon model to mimic the distal part of human large intestine. This batch culture system allows rapid response in monitoring performance of acacia gum fermented by beneficial colonic microbes such as bifidobacteria and lactobacilli. Inoculation of gut microbiota from human faeces into the model start the fermentation system, continuously administered with automated pH-controller maintained at 37ºC. Samples taken at 0, 6, 12, and 24 hours of incubation were brought for short chain fatty acids (SCFA) analysis using HPLC and bacterial enumeration via fluorescent in situ hybridization (FISH) methods. Experiment were repeated four times with fructo-oligosaccharides (FOS) as control. Results showed that acacia gum significantly promoting Bifidobacteria proliferation at the end of fermentation to the same extend benefit of that in FOS while significantly inhibit the growth of pathogenic Clostridium histolyticum group which can be an important target group commonly associate with gut dysbiosis. The metabolites analysed for acetate, propionate, and butyrate showed a similar trend as FOS (p > 0.05). Further evaluation of AG was observed in the independent enrichment culture study of acacia gum. Five bacteria strains were isolated ought to be gum-fermenting bacteria of which based on 16s RNA sequence result matched to Escherichia fergusonii. Here, isolated Escherichia fergusonii shows butyrate producing activity while fermenting AG. This effects may have related to the lowering pH regards to organic acid production. Finally, further investigation to evaluate the isolates and probiotic bacteria associated in a co-culture environment. The symbiotic combination led to increase acetate and overall SCFA production. This effect was more apparent than with the isolates, or probiotic alone treatments. In monoculture of probiotic, it showed that Bifidobacteria longum alone does not strive in acacia gum medium whereas co-culture of probiotics and isolated strain showed otherwise. In conclusion, the potential of AG as a prebiotic has been explored. Furthermore, a conceptual relationship has been developed during the co-culture fermentation. These products could show great potential against gut dysbiosis, as acacia gum could promote native gut-probiotics, through the modulation of microbial population and SCFA production especially butyrate, therefore lead to improve overall human health.